2021
DOI: 10.1177/2396987321997045
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic rules for predicting cognitive syndromes following stroke: A systematic review

Abstract: Purpose Stroke survivors are at high risk of developing cognitive syndromes, such as delirium and dementia. Accurate prediction of future cognitive outcomes may aid timely diagnosis, intervention planning, and stratification in clinical trials. We aimed to identify, describe and appraise existing multivariable prognostic rules for prediction of post-stroke cognitive status. Method We systematically searched four electronic databases from inception to November 2019 for publications describing a method to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Our literature review was based on a recent systematic review [150] and found seven prognostic tools [151][152][153][154][155][156][157] that had been applied in an acute stroke population and were designed to predict a variety of future cognitive outcomes. Eligible studies were from Europe and Asia and included a variety of stroke types.…”
Section: Analysis Of the Current Evidencementioning
confidence: 99%
“…Our literature review was based on a recent systematic review [150] and found seven prognostic tools [151][152][153][154][155][156][157] that had been applied in an acute stroke population and were designed to predict a variety of future cognitive outcomes. Eligible studies were from Europe and Asia and included a variety of stroke types.…”
Section: Analysis Of the Current Evidencementioning
confidence: 99%
“… 22 Prognostic models, specific to the stroke population are being developed, however, international guidelines on post-stroke cognitive impairment recognise that there are currently no tools suitable for use in clinical practice. 7 , 27 Should a risk prediction tool be suitable for use in clinical practice, it is important that the ethics of discussing risk of dementia are carefully considered. A previous study explored the feasibility of using a prediction tool for dementia as part of follow-up care for people who have a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no robust prognostic tools that accurately predict which stroke patients are at risk of developing post-stroke dementia. 7 A qualitative study used semi-structured interviews to assess the acceptability to patients, carers, and clinicians of using dementia risk prediction tools as part of post-stroke follow-up care. 8 This study interviewed 15 stroke patients and their carers (at six and twelve months post-stroke) and 17 clinicians, in the North East of England.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, stroke clinicians are now shifting their focus to improvements in rehabilitation and post-acute care (63)(64)(65)(66). Post-stroke cognitive impairment is identified as a key priority area for research and support by stroke survivors, but predictive models for individualised risk factors for cognitive decline are sorely needed (67). In other neurodegenerative diseases causing dementia, there is a strong association between brain atrophy and cognitive decline: neurodegeneration precedes and predicts the onset of cognitive impairment (68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%